2007
DOI: 10.1557/jmr.2007.0146
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic chemical vapor deposition of carbon-free ZnO using the bis(2,2,6,6-tetramethyl-3,5-heptanedionato)zinc precursor

Abstract: Bis(2,2,6,6-tetramethyl-3,5-heptanedionato)zinc [Zn(TMHD) 2 ] is a relatively uninvestigated precursor that was used in this work to grow highly c-axis-oriented ZnO films on Si(100). X-ray photoelectron spectroscopy studies before and after Ar ion sputtering indicated that surface carbon on several samples was reduced from as much as 34 at.% to much less than 1 at.% within the first 5 nm, indicating very clean Zn(TMHD) 2 precursor decomposition. Microstructural and compositional analysis revealed columnar ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Therefore, alternative precursors were considered for ALD of ZnS in this work. The precursor chosen for zinc was bis(2,2,6,6-tetramethyl-3,5-heptanedionato)zinc [Zn(TMHD) 2 ], because it is a nonpyrophoric solid precursor used for the chemical vapor deposition of zinc oxide 20 and has been used for ALD of ZnS in previous work. 21 While precursors typically used for the deposition of Cu 2 S do not necessarily have the same safety considerations as DEZn [e.g., the low-toxicity, nonflammable Cu 2 (DBA)], 22 the precursor chosen for copper in this study was Bis(2,2,6,6-tetramethyl-3,5-heptanedionato)copper (Cu(TMHD) 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative precursors were considered for ALD of ZnS in this work. The precursor chosen for zinc was bis(2,2,6,6-tetramethyl-3,5-heptanedionato)zinc [Zn(TMHD) 2 ], because it is a nonpyrophoric solid precursor used for the chemical vapor deposition of zinc oxide 20 and has been used for ALD of ZnS in previous work. 21 While precursors typically used for the deposition of Cu 2 S do not necessarily have the same safety considerations as DEZn [e.g., the low-toxicity, nonflammable Cu 2 (DBA)], 22 the precursor chosen for copper in this study was Bis(2,2,6,6-tetramethyl-3,5-heptanedionato)copper (Cu(TMHD) 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 The objective of this research was to examine the viability of Zn(TMHD) 2 as a precursor for atomic layer deposition, and to discover the ideal parameters for such a process.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Bis(2,2,6,6-tetramethyl-3,5-heptanedionato)zinc [Zn(tmhd) 2 ] is a relatively unstudied precursor that has been recently applied to the deposition of ZnO. [28] Recently, we have obtained ZnO thin films deposited by MOCVD using the novel diamine (N,N,N 0 ,N 0 -tetramethylethylenediamine) adduct of zinc bis-2 thenoyltrifluoroacetonate [Zn(tta) 2 tmeda]. [29] Preliminary studies have shown that this precursor is suited to the deposition of ZnO thin films onto quartz substrates.…”
Section: Introductionmentioning
confidence: 99%